SINTESIS DAN UJI AKTIVITAS PENGHAMBATAN POLIMERISASI HEM SENYAWA 3-HIDROKSI-6-METILSANTON - , PRESTIKA GEMA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Synthesis of 3-hydroxy-6-methylxanthone from resorcinol and m-cresol has been conducted. Heme polymerization inhibitory activity assay of the synthesized antimalarial has also been carried out. Synthesis of antimalarial of xanthone derivative was conducted in two steps. The first step of reaction was carboxylation of resorcinol via Kolbe reaction, resorcinol was refluxed with aqueous solution of potassium bicarbonate in the presence of carbon dioxide (CO2) then acidified by hydrogen chloride to provide 2,4-dihydroybenzoic acid compound in the form of a white solid with percent yield and melting point respectively 40.64% and 213.7â217.6 Â°C. The final step, carboxylation product 2,4-dihydroxybenzoic acid was reacted with m-cresol. The mixture was heated with Eatonâs reagent at 70â80 Â°C for 3 hours to yield 3-hydroxy-6-methylxanthone (76.7%) as a brown oily solid. The structures of products were characterized by IR, MS and 1H-NMR spectrometers. The results of heme polymerization inhibitory activity assay of 6-hydroxy-3-methylxanthone was determined by standard curve as the reference. The results showed that 3-hydroxy-6-methylxanthone had IC50 HPIA of 8.85 Ã 10-3 mM, while chloroquine had IC50 0.172 mM. These results indicated that 3-hydroxy-6-methylxanthone is a potential antimalarial agent rather than chloroquine 0.172 mM